An Analysis of Students' Perception Toward TikTok Educational Content for English Language Learning - Parwansah, Kaviva Indah; Arafiq; Wardana, Lalu Ali; Elmiana, Dewi Satria (Journal of Authentic Research, 2026)
This study aims to analyze students' perceptions toward TikTok educational content for English language learning. This research employed a mixed-method approach by combining quantitative and qualitative data. The respondents of this study were students from various study programs at Mataram University who actively use the TikTok application. The total number of respondents was 65 students. Data were collected through a questionnaire using a Likert scale (1=Strongly Disagree to 5=Strongly Agree) and interviews with several selected respondents. The quantitative data were analyzed using descriptive statistics (frequency, percentage, and mean scores) with the help of SPSS version 26, while the qualitative data were analyzed using the Miles and Huberman model (data reduction, data display, and conclusion drawing). The results of the questionnaire analysis showed that students generally have positive perceptions toward TikTok educational content for English language learning, with an overall mean score of 3.89 out of a maximum score of 5, falling into the positive category. Most students agreed that TikTok can help them improve their English skills, particularly vocabulary, pronunciation, and grammar. In addition, the short video format, attractive visual presentation, and creative content make the learning process more interesting and engaging. Students also perceived TikTok as a flexible learning platform because it can be accessed anytime and anywhere. However, some respondents mentioned that internet connection problems and distractions from entertainment content may become challenges in using TikTok as a learning medium. Overall, TikTok educational content has the potential to support English language learning in informal learning environments.